2022
DOI: 10.1038/s41598-022-06119-5
|View full text |Cite
|
Sign up to set email alerts
|

Demarcating the boundary conditions of memory reconsolidation: An unsuccessful replication

Abstract: Disrupting memory reconsolidation provides an opportunity to abruptly reduce the behavioural expression of fear memories with long-lasting effects. The success of a reconsolidation intervention is, however, not guaranteed as it strongly depends on the destabilization of the memory. Identifying the necessary conditions to trigger destabilization remains one of the critical challenges in the field. We aimed to replicate a study from our lab, showing that the occurrence of a prediction error (PE) during reactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, some studies also failed to show the effect of memory reconsolidation [ 17 , 27 , 28 ]. The inconsistency in successfully replicating the memory reconsolidation reactivation paradigm might be due to boundary conditions [ 29 ]. Boundary conditions refer to circumstances that can either exhilarate or oppress a process [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some studies also failed to show the effect of memory reconsolidation [ 17 , 27 , 28 ]. The inconsistency in successfully replicating the memory reconsolidation reactivation paradigm might be due to boundary conditions [ 29 ]. Boundary conditions refer to circumstances that can either exhilarate or oppress a process [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistency in successfully replicating the memory reconsolidation reactivation paradigm might be due to boundary conditions [ 29 ]. Boundary conditions refer to circumstances that can either exhilarate or oppress a process [ 29 ]. In the context of memory reconsolidation, boundary conditions refer to the factors that influence whether a particular memory will undergo reconsolidation and the extent to which it can be modified.…”
Section: Introductionmentioning
confidence: 99%
“…These studies typically find that the reconsolidation process of the original fear memory is impaired, thereby interrupting fear response mechanisms. However, there is also evidence that pharmacological reconsolidation interference is not always obtained both in animals 8 and humans 9 , 10 , and it has been shown that there is a publication bias in the literature towards presenting evidence of reconsolidation interference 11 .…”
Section: Introductionmentioning
confidence: 99%
“…This led to the proposal of socalled 'boundary conditions' which were defined as "physiological, environmental or psychological situations in which memory that normally would reconsolidate does not"(Nader & Hardt, 2009, page 228;Duvarci, Ben Mamou, & Nader, 2006). Furthermore, whilst establishing the generality and limits of cue-dependent amnesia, recent studies have sometimes failed to replicate pharmacological (e.g.,Luyten, Schnell, Schroyens, & Beckers, 2021;Schroyens, Alfei, Schnell, Luyten, & Beckers, 2019;Schroyens, Beckers, & Kindt, 2017;Stemerding, Stibbe, van Ast, & Kindt, 2022) and non-pharmacological induction of cue-dependent amnesia (e.g.,Chan, Leung, Westbrook, & McNally, 2010;Jaswetz, de Voogd, Becker, & Roelofs, 2022;Luyten & Beckers, 2017) in both humans and non-human animals. This has inspired further discussions regarding potential 'boundary conditions' that might affect the reliability and efficacy of these procedures (for reviews, see…”
mentioning
confidence: 99%